Urban Public Transportation and Firm Location Choice Evidence from the Regional Express Rail of Paris Metropolitan area - Corentin Trevien; Thierry Mayer (European Regional Science Association (ERSA), 2013)
This paper identifies the causal impact of urban rail transport on firm location. The evaluation of transport infrastructures always faces an important issue of endogeneity since rail lines are not randomly located. We use the natural experiment offered by the Regional Express Rail (RER) in the Paris metropolitan region, which widely improved the commuter train system. We provide two strategies to address the endogeneity issue. The RER network has been implemented with the aim of connecting 'new towns' located 30 km away from the historic center of Paris. Commuter train crosses municipalities located between the historical core and the five new towns of the metropolitan area. These municipalities are 'quasi-randomly' treated and can be compared to similar untreated municipalities in order to estimate the causal impact of railway infrastructures. The second strategy relies on significant differences between the initial plan presented in 1965 and the current network. We combine this rigorous approach of transport infrastructure evaluation with a standard frame of firm location choice. More concretely, we consider both domestic and foreign firm location choices across municipalities of the Paris metropolitan region. In addition to basic criterions as market potential, agglomeration, labor costs and land rent, we add the proximity to a commuter train station and an accessibility index based on travel time variation by public transport. We show that ignoring the endogeneity issue doubles or triples the estimated impact of rail on the market share in firm location of a municipality. The regional market share of a municipality in firm location increases between 4 and 6 % with a station. However, the total number of firms grows durably only if the travel time decreases. Indeed, the quality of the rail connection matters: the more the reduction of time associated with the opening of a new station is high the more the effect of transportation on firm location is important and durable. In addition, the impact of the RER is very strong for foreign firms: FDI location increases by 18 % with the opening of a RER station. Finally, the effect varies across industry sector and turns out to be higher for business services and household services.
Keywords: D04; H43; R42; 330